LAJU DEKOMPOSISI LIMBAH DAUN KAYU PUTIH SEBAGAI BAHAN BAKU KOMPOS PADA KPH BURU - Aristo C Pattinasarani; Ludia Siahaya; Febian Filiph Tetelay (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
The purpose of this study was to determine the effect of giving an EM4 bio-activator on the rate of decomposition of cajuput leaf waste at KPH Buru. This study used a Quantitative Descriptive method by comparing the properties of compost made with SNI. The composting method uses the Indore Pit Method. The materials used in this study were waste from the cajuput oil distillation process which was given treatment A (without EM4), treatment B (10 ml EM4), C treatment (20 ml EM4), and D treatment (30 ml EM4). The results showed that the average rate of decomposition in treatment A was 83.4 grams/week, treatment B was 141.7 grams/week, treatment C was 239.6 grams/week and treatment D was 500 grams/week. This shows that the fastest decomposition rate was given 30 ml of EM4 bio-activator with a decomposition rate of 500 grams/week.